A simple, fast and inexpensive method for mutation scanning of CFTR gene - Juan Emilio Figueredo Lago; Anny Armas Cayarga; Yaimé Josefina González González; Teresa Collazo Mesa (BMC, 2017)
Abstract Background Mutation scanning methods in Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene may not distinguish between a Cystic Fibrosis (CF) causing mutation and a benign variant. We have developed a simple and fast method for scanning 14 selected CF-causing mutations which have high frequency in Latin America. Methods In a group of 35 samples coming from CF patients previously characterized and using two allele-specific real-time multiplex PCRs targeting wild-type and mutant alleles respectively, we detect the presence of mutations by analyzing the Ct variation. Twenty-five samples without mutations considered non-carrier samples, were also included in this study. High Resolution Melting Analysis (HRMA) was performed to confirm the result of the scanning method and in most cases allowed the genotype determination. Results The results validate this method for CF diagnosis. A least one CFTR gene mutation was detected in the samples of CF patients, as predicted by their ΔCt values. The ΔCt value also indicated the zygosity of the sample according to the distribution of CFTR gene mutations. In most cases, HRMA allowed the identification of the mutation(s), thereby confirming the efficiency of this scanning strategy. Conclusions This strategy simplifies the detection of CF, reducing the analysis of 14 CF-causing mutations to two parallel reactions and making the procedure compatible with the analysis of a large number of samples. As the method is fast, inexpensive and highly reliable, it is advisable for scanning CFTR gene mutations in newborns, patients with a clinical suspicion of CF as well as in the preconception carrier screening.